2019
DOI: 10.32098/mltj.02.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers’ perceptions of their scoliotic curves. Comparison between sports people and non-sports people

Abstract: Background. Idiopathic scoliosis is a disease caused by a deformity of the spine and is frequently found during adolescence. Sports, and so the training of motor skills and proprioception, could have a positive influence on the perception of the body schema and scoliotic deformity. Methods. We designed an observational study in which we recruited young patients with scoliosis. Analysis of the scoliotic radiographic curve was conducted with specific radiograph examination. The giving of the spine silhouette to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Cabarkapa et al, 28 in a systematic review, showed evidence that female subjects appeared to have the highest mental health risks 41 , 45 and specifically, being a female HCWs conferred greater risks for depression, anxiety, and higher levels of stress. 57 , 58 , 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabarkapa et al, 28 in a systematic review, showed evidence that female subjects appeared to have the highest mental health risks 41 , 45 and specifically, being a female HCWs conferred greater risks for depression, anxiety, and higher levels of stress. 57 , 58 , 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the female condition, our data are consistent with other studies such as Rossi et al 14 In this study, depressive symptoms were associated with some specific aspects, including being a woman. Cabarkapa et al, 28 in a systematic review, showed evidence that female subjects appeared to have the highest mental health risks 41,45 and specifically, being a female HCWs conferred greater risks for depression, anxiety, and higher levels of stress 57–60 …”
Section: Discussionmentioning
confidence: 99%
“…It was found that they tend to overestimate the severity of their scoliosis. The perception of their body schema and spinal curvature can be improved by enhancing motor skills through participation in physical activity [33]. The potential psychological benefits brought about by the E-Fit came as a surprise in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…This evidence is in line with the current scientific literature. In fact, MP is more frequent in high frequency and intensity sports [17,18] and in long sports practice [17]. In 2016, Kamada et al [19] carried out research into the dose-response relationship between sports activity and MP in adolescents and found that each additional 1 h/wk of sports activity was associated with a 3% higher probability of having pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this sports practice, that usually begins at an early age, lasts throughout the growth period, including the phases of rapid growth [18]; consequently, gymnasts are exposed to injuries and to the onset of musculoskeletal pain (MP) [10] related to sports practice.…”
Section: Introductionmentioning
confidence: 99%